A review of the dielectric properties of the bone for low frequency medical technologies. (7th January 2019) - Amin, Bilal; Elahi, Muhammad Adnan; Shahzad, Atif; Porter, Emily; O'Halloran, Martin
Abstract: The dielectric properties are key parameters that quantify the interaction between electromagnetic waves and human biological tissues. In particular, the development of electromagnetic-based medical technologies rely on knowledge of the dielectric properties of bone, specifically for applications such as electrical stimulation and bone health monitoring. Electrical stimulation is used in clinics to promote the healing of bone fractures, treating non-unions, congenital pseudarthrosis, bone regeneration and during bone implant procedures. The response of the bone to any external electrical stimulation is governed by the dielectric properties of the bone, which vary with the applied frequency of the stimuli. Bone mineral density is considered a key indicator of osteoporosis diagnosis, and is assumed to be related to the dielectric properties of the bone. Therefore, dielectric properties of bones may potentially be used to diagnose osteoporosis. The bone dielectric properties can be assessed non-invasively for bone health monitoring. Several research studies have reported dielectric properties of cortical and trabecular bones in recent literature. Since dielectric properties of bone determine the response of the tissue to therapies, it is important to compile and analyze the reported dielectric data in order to have a thorough understanding of these properties. It is established from the literature that the low frequency (10 Hz–1 GHz) dielectric properties of bone are particularly important in diagnostic applications, as the correlation between the dielectric properties and bone mineral density is more significant than at higher frequencies. In this paper, the low frequency dielectric properties of the bone reported in the literature are compiled and quantitatively analysed. The results suggest that there is a significant inter- and intra-species variation in the reported dielectric data from human, bovine, porcine, and rat bone tissues. Moreover, the relationship between the dielectric properties and bone mineral density is inconsistent across the various studies, indicating that further research in this area is needed.